Studi Literatur: Analisis Implementasi Tahapan-tahapan Pembelajaran Bilingual di Sekolah Dasar - Sholikha, I’malus; Aini, Intan Nur; Ramadhani, Niken Aulia; Oktavianingrum, Berliana Aurora; Rosyida, Helmilia Qilla Fatur; Wahyuningsih, Fitri; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of bilingual learning at the elementary school level in Indonesia. This study uses a qualitative descriptive approach with a literature study method. Data were collected from various relevant sources, such as scientific journals, articles, and books, then analyzed using descriptive analysis techniques. The results of the study indicate that bilingual learning is implemented through the main stages, namely planning, implementation, and evaluation. Case studies from various elementary schools show that the implementation of bilingual programs varies, depending on the conditions and characteristics of the institution and students. This program has been proven to be able to improve students' foreign language skills, such as listening, speaking, reading, and writing skills, while supporting the achievement of educational goals in the era of globalization. However, its implementation is not free from obstacles, such as limited facilities, differences in language abilities between students, and lack of teacher training. Therefore, a deep understanding of implementation strategies and practices is essential so that bilingual learning can be implemented effectively and sustainably in the context of elementary education in Indonesia.